NILAI SUSILA PADA TOKOH MAGI DIELA DALAM NOVEL PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM KARYA DIAN PURNOMO - Robyatul Hasanah; Abdoel Gafar (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the moral value of conveying the life phenomenon of the character Magi Diela in the novel is something amazing to guide the reader's life values. Therefore, the author is interested in analyzing the novel Perempuan yang Menangis Kepada Bulan Hitam Karya Dian Purnomo. Moral values come from conscience, even though it is not written, this norm exists in the human heart, this value distinguishes between right and wrong, guiding daily life according to human nature. The type of research used in this study is descriptive research. The approach used is qualitative. Qualitative is a research approach that the author will use in processing data. Based on the research that has been conducted on the Novel Perempuan yang Menangis Kepada Bulan Hitam Karya Dian Purnomo about the form of moral value of Magi Diela's character, the research results can be obtained as follows: (1). Fairness is obtained as many as 11 quotes, (2) Honesty is obtained as many as 10 quotes, (3). Help each other is obtained as many as 13 quotations, then the total number of quotations obtained is 34 quotations. So it can be concluded that the character of Magi Diela is a figure who can be emulated and inspired to fight for women's right